Pretreatment of oil palm lignocellulosic biomass using 1-ethyl-3-methylimidazolium acetate / Intan Suhada Azmi - Azmi, Intan Suhada (2018)
Lignocellulosic biomass has a great potential to be a prospective renewable resource that can be used for the generation of bioethanol, Oil palm biomass was chosen as it is one of the most abundances residues in Malaysia. The major concern in lignocellulose conversion is overcoming biomass recalcitrance through pretreatment while still maintaining a green engineering method, an energy efficiency and an economically feasible process. Recent development showed that ionic liquids can be utilized to treat lignocellulosic biomass efficiently, however, the drawback of using pure ionic liquid is its expensive cost and also extremely viscous. Therefore, this research investigated on the use of aqueous IL during pretreatment. The ionic liquid used was 1-ethyl-3- methylimidazolium acetate [EMIM] Ac and the raw materials were Microcrystalline Cellulose (MCC) and Oil Palm Frond (OFF). The effect of [EMIM]Ac concentration [0-100%], temperature (70-99°C) and dissolution time (1-3 hours) on pretreatment of lignocellulosic biomass was analysed by Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM), It was found that the optimum conditions for the pretreatment is 50-100% [EMIM]Ac concentration, temperature of 99°C and dissolution time of 3 hours. Based on peak analysis and Lateral Order Index (LOI) value, Crystallinity Index (CI) value and the changes of morphology. The effect of increasing concentration, temperature and time decreased LOI and CI values indicating reduction in the degree of crystallinity and increased of amorphousity of the MCC and OPF sample, The LOI and CI values for OPF pretreated with 10% [EMIM] Ac are 1.02 and 0.45 where it decreased to 0.24 and 0.28, respectively after concentration of [EMIM] Ac was increased to 100%. The same trend was observed for effect of temperature where the LOI and CI values for OPF pretreated with 50% [EMIM] Ac at temperature of 70°C which are 0.97 and 0.46 were decreased to 0.61 and 0.38, respectively after pretreated with 50% [EMIM]Ac at temperature of 99°C. Moreover, the LOI and CI values for OPF pretreated with 50% [EMIM] AC for 1 hour’s dissolution time are 1.05 and 0.48 where it decreased to 0.48 and 0.38, respectively after the dissolution time was increased to 3 hours. The findings from SEM support the FTIR and XRD results as the pretreated sample structure became cracked and disordered while the raw sample have a smooth structure. Based on the optimum condition studied, the pretreatment was also conducted by using Oil Palm Trunk (OPT) and Empty Fruit Bunch (EFB). It is proven that aqueous [EMIM] Ac starting with 50% to 90% concentration can disrupt the cellulose structure. Therefore, it is feasible to employ aqueous [EMIM] AC in the range of 50-90% concentration in order to achieve efficient dissolution in an economically viable pretreatment.